Inhibition of the futalosine pathway for menaquinone biosynthesis suppresses Chlamydia trachomatis infection. Issue 24 (16th November 2021) - Dudiak, Brianne M.; Nguyen, Tri M.; Needham, David; Outlaw, Taylor C.; McCafferty, Dewey G.
Abstract : Chlamydia trachomatis, an obligate intracellular bacterium with limited metabolic capabilities, possesses the futalosine pathway for menaquinone biosynthesis. Futalosine pathway enzymes have promise as narrow‐spectrum antibiotic targets, but the activity and essentiality of chlamydial menaquinone biosynthesis have yet to be established. In this work, menaquinone‐7 (MK‐7) was identified as a C. trachomatis ‐produced quinone through liquid chromatography‐tandem mass spectrometry. An immunofluorescence‐based assay revealed that treatment of C. trachomatis ‐infected HeLa cells with the futalosine pathway inhibitor docosahexaenoic acid (DHA) reduced inclusion number, inclusion size, and infectious progeny. Supplementation with MK‐7 nanoparticles rescued the effect of DHA on inclusion number, indicating that the futalosine pathway is a target of DHA in this system. These results open the door for menaquinone biosynthesis inhibitors to be pursued in antichlamydial development. Abstract : The bacterial pathogen Chlamydia trachomatis harbors the futalosine pathway for biosynthesis of the electron carrier menaquinone. In this work, menaquinone‐7 was identified as a pathway product by liquid chromatography‐tandem mass spectrometry. Inhibition of the futalosine pathway in C. trachomatis ‐infected HeLa cells with docosahexaenoic acid was discovered to disrupt inclusion formation. These results lay the foundation for exploring menaquinone biosynthesis enzymes as antichlamydial targets.